THE IMPACTS OF SOCIAL SUPPORT TYPES AND SOURCES ON PSYCHOLOGICAL OWNERSHIP - Anil Boz Semerci; Azize Ergeneli (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The purpose of this paper is to understandthe impact of types and sources of social support on psychological ownershipand to attempt to extend the empirical evidence on the predictors ofpsychological ownership of employees. This study draws on data from employeesworking in private sector in Turkey. The quantitative research method was used.Drawing on the data of 277 employees, variables’ factorial structures were testedusing confirmatory factor analysis and hypotheses were tested with hierarchicalregression analysis. The results reveal that the relationship of psychologicalownership and social support varies according to types and sources of socialsupport. Given the importance of psychological ownership for businesses, thefindings of this study have significant contributions and suggestions forfurther empirical studies, in addition to its practical value on managers andemployees.